Impelementasi Kriptografi RSA dan XOR Cipher untuk Enkripsi Citra Digital KTP - Artajaya, Gede Krisna Surya; Muliantara, Agus (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 2 No 4 (2024): JNATIA Vol. 2, No. 4, Agustus 2024DO - 10.24843/JNATIA.2024.v02.i04.p01, 2024)
The advancement of technology has led to innovative solutions in administrative sectors, exemplified by the introduction of “KTP Digital”. However, not everyone has adopted “KTP Digital” and is still relying on scanned copies of identity cards that can expose digital image data to security vulnerabilities. This study addresses these vulnerabilities by proposing encryption techniques. Utilizing RSA and XOR Cipher algorithms, this research demonstrates effective encryption and decryption of digital image data. Evaluation metrics, including Peak Signal-to-Noise Ratio (PSNR), confirm minimal similarity between plain and cipher images, indicating robust encryption. Specifically, PSNR values for plain vs. cipher images range from 7 to 8 dB, well below 10 dB, indicating a very significant difference. Additionally, high PSNR values between original and decrypted plain images, which is 100 dB, suggest negligible data alteration post decryption confirming that the decryption process successfully restores the image to its original state.